2011
DOI: 10.2174/156720111793663651
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy of Solid Tumors: Searching for the Right Target

Abstract: Radioimmunotherapy of solid tumors remains a challenge despite the tremendous success of 90Y ibritumomab tiuxetan (Zevalin) and 131I Tositumomab (Bexxar) in treating non-Hodgkin’s lymphoma. For a variety of reasons, clinical trials of radiolabeled antibodies against solid tumors have not led to responses equivalent to those seen against lymphoma. In contrast, promising responses have been observed with unlabeled antibodies that target solid tumor receptors associated with cellular signaling pathways. These obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 144 publications
(123 reference statements)
1
43
1
1
Order By: Relevance
“…At therapeutic activities of 177 Lu (400 MBq/kg), the decrease in peripheral leukocytes (22) probably results in an impaired immune response. Instead, with absorbed-dose rates and total absorbed doses approximately 8 times higher than in this study, radiation-induced cell death might dominate in achieving complete response (31). Calculations of absorbed-dose rate distributions at different time points showed that high-uptake regions have twice the absorbed-dose rate of the whole tumor section mean.…”
Section: Discussioncontrasting
confidence: 57%
“…At therapeutic activities of 177 Lu (400 MBq/kg), the decrease in peripheral leukocytes (22) probably results in an impaired immune response. Instead, with absorbed-dose rates and total absorbed doses approximately 8 times higher than in this study, radiation-induced cell death might dominate in achieving complete response (31). Calculations of absorbed-dose rate distributions at different time points showed that high-uptake regions have twice the absorbed-dose rate of the whole tumor section mean.…”
Section: Discussioncontrasting
confidence: 57%
“…Radiolabelled peptides targeting receptor molecules overexpressed on tumour cells include ligands (or antagonists) of the somatostatin receptor [29,30], the cholecystokinin 2/gastrin receptor, the glucagon-like peptide-1 receptor, the neurokinin type-1 receptor, the neurotensin receptor and the gastrin-releasing peptide receptor, to name just a few [20,31]. Radionuclides targeted with antibodies have been administered in numerous tumours showing overexpression or exclusive expression of tumour surface antigens [32][33][34]. Radionuclides used for targeted therapy predominantly include β-emitters such as 131 I, 177 Lu and 90 Y due to their good availability and ease of handling.…”
Section: Discussionmentioning
confidence: 99%
“…In the control group treated with PBS, the tumour mass linearly increased until the animals were killed. In contrast, in mice treated with 213 Bi-DTPA-F3, the tumour mass initially increased until 1-8 days after the last treatment (days [28][29][30][31][32][33][34][35] and then declined until a minimum was reached 29 days after the last treatment (day 56; Fig. 3a).…”
Section: Monitoring Of Tumour Development By Bioluminescence Imagingmentioning
confidence: 99%
“…Auger-electron emitters are attractive candidate radionuclides in TRT of disseminated diseases (and micrometastasis) due to a vanishing cross-irradiation effect which spares healthy cells in the vicinity of the targeted cells (Fischer et al, 2008;Kassis, 2011Kassis, , 2004Yasui, 2012). It has been reported (Behr et al, 2000;Boswell and Brechbiel, 2005) that Auger emitters (I-125, In-111) may exhibit better therapeutic effect, when bound to an internalizing monoclonal antibody, than β À -emitters (I-131, Y-90) which have been used successfully in the treatment of non-Hodgkins' lymphoma Pouget et al, 2011;Song and Sgouros, 2011).…”
Section: Introductionmentioning
confidence: 99%